FACTOR INFLUENCING DECISION MAKING MODEL FOR THE ESTIMATION OF COMPETITIVE EFFECTIVENESS AMONG THIRD‐PARTY LOGISTICS PROVIDER - Narasimharajan, M; Venkatesan, R (The South African Journal of Industrial Engineering, 2022)
In the modern supply chain management (SCM) environment, Logistics provider-selection is the most critical decision making process, for which the existing literatures enumerate several criteria, that need to be simplified with scientific approach based on analysis. This investigation explores and illustrates the effects of the selected factors for an evaluation of the competitive effectiveness among third‐party logistics (3PL) providers, through a managerial perspective, focusing on the various decision making aspects (DMA). In order to rank the criteria, a self administered and a well structured questionnaire had been used to gather the primary data. The findings analyzed by using Smart PLS to draw the inferences from the research study. An Analytical hierarchical process applied to ranking the criteria and the position has been compared with the convenience sampling method. The framework provided can help the industry leaders to conceptualize, enlarge and to learn the strategies to be adopted for recognizing the 3PL providers.